Answer:
that is a whole lot of simple intrest
Answer:
B.
Step-by-step explanation:
The negative of a negative is a positive, so B is your choice. Think of it anothe way, if it helps. Imagine that the expression is this:
(-2) + (-1)(-3) since every subtraction problem can be rewritten as an addition problem.
We would first, by orders of operation, multiply the -1 and the -3 getting 3. Then the problem would simplify down to -2 + 3
Just another idea to ponder...
<em>P = a + b + c = 49 cm</em>
<em>a = b + 7 => b = a - 7</em>
<em>a = c - 5 => c = a + 5</em>
<em>_____________________</em>
<em>a + (a - 7) + (a + 5) = 49</em>
<em>3a = 49 + 7 - 5</em>
<em>3a = 51 </em>
<em>a = 17 cm</em>
<em>b = 17 - 7 = 10 cm</em>
<em>c = 17 + 5 = 22 cm</em>
Answer:
Kx20=N
Step-by-step explanation:
k with be the number multiplied by 20 and then N will be the answer